Oral Health-Related Quality Of Life in Geriatric Patients: A Narrative Review - Khare, Anshika; Gupta, Ankita (Journal of Orofacial Research, 2018)
An oral cavity is an imperative part of our body, which has a noteworthy role in chewing, swallowing, speech, nutritional status, facial expression as well as self-reliance. Thus, oral health significantly related to the quality of life. Geriatric patients make a significant group of our community have a high prevalence of oral diseases including root caries, periodontal problems, edentulousness, dry mouth etc. Dental needs of geriatric patients are a very sensitive issue due to its critical management that requires an understanding of medical as well as dental aspects of aging. Therefore, this review aims to assess oral health-related quality of life among the geriatric population and the data obtained from the published articles, books and online manuals.